Long-term storage and subsequent reactivation of Anammox sludge at 35˚C. Issue 52 (7th November 2016) - Wang, Tao; Zhang, Hanmin; Yang, Fenglin
Abstract: The feasibility of a long-term storage and subsequent reactivation of Anammox sludge was investigated. The storage strategy was improved for a long-term storage. The storage at an optimized temperature (35°C) for growth and metabolism of Anammox bacteria was attempted to retain Anammox activity for acceleration of the reactivation process after the storage. During the storage, a little of Anammox nutrient medium containing 50 mg-N l −1 (NH4 )2 SO4 and NaNO2 was added and periodically (every week) refreshed to keep the survival of Anammox bacteria. After the 6-month storage, there was still an Anammox activity of 0.07 g ( -N +  -N) (gVSS × d) −1, even though most Anammox bacteria were in dormant state. The reactivation of the stored Anammox sludge was achieved in an SBR after a 2-month operation, and the final nitrogen removal rate of 0.32 g ( -N +  -N) L −1  d −1 was gained. Compared with the fresh activated sludge, the stored Anammox sludge could realize a quick start-up of Anammox process. The results demonstrated that the improved storage strategy was suitable for a long-term storage and subsequent reactivation of Anammox sludge.